2009
DOI: 10.1007/s10067-009-1173-4
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell membrane in the treatment of pain and stiffness from osteoarthritis of the knee: a randomized, multicenter, double-blind, placebo-controlled clinical study

Abstract: Natural Eggshell Membrane (NEM®) is a new novel dietary supplement that contains naturally occurring glycosaminoglycans and proteins essential for maintaining healthy articular cartilage and the surrounding synovium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
52
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 29 publications
(22 reference statements)
9
52
0
2
Order By: Relevance
“…And almost 20% of the study population experienced a 50% improvement in pain-related questions by the end of the study (60 days) (not shown). These results align well with results from previous clinical studies of NEM ® that were conducted in the U.S. [6,7].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…And almost 20% of the study population experienced a 50% improvement in pain-related questions by the end of the study (60 days) (not shown). These results align well with results from previous clinical studies of NEM ® that were conducted in the U.S. [6,7].…”
Section: Discussionsupporting
confidence: 90%
“…In previous trials with NEM ® [6,7], the standard deviation for the study subjects for pain (within the inclusion range of this study) averaged 34.6%. We hoped to be able to detect a 1.5 point difference from baseline within the 10-point Likert scale.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The eggshell membrane is one of the food supplements that have had very good results in this sense [2][3][4][5]. Eggshell membrane is comprised of a large part of collagen, mainly type I, V and X [6][7][8]; glycosaminoglycans (hyaluronic acid, chondroitin sulfate and different proteins that are involved in the antiinflammatory and immune system regulation ability of the eggshell membrane (lysozyme, ovotransferrin, ovocleidin-17 and ovocleidin-116) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Eggshell membrane is primarily composed of fibrous proteins such as collagen type I. 7 However, eggshell membranes have also been shown to contain glycosaminoglycans, such as dermatan sulfate, chondroitin sulfate, 8 and hyaluronic acid, 9 and sulfated glycoproteins, including hexosamines such as glucosamine.…”
Section: Introduction Tmentioning
confidence: 99%